The Australian Pastures Genebank - A short history and update of progress - Hughes, S; Rowan Smith; Cox, K; Humphries, A; McClements, D; Harris, C; Rogers, M-J (2017)
The Australian Pastures Genebank (APG), Australia’s first national genebank housing pasture and forage genetic resources was officially launched in December in 2014 at the South Australian Research and Development Institute’s Waite Campus in Adelaide. Over the last two years, pasture and forage genetic resources from major temperate pasture and tropical forage genebanks around the country have been transferred to the national collection. More than 83,400 accessions, including approximately 75,000 unique accessions (found in no other genebanks) are now under one roof. An assessment of the collection’s health is underway along with the prioritisation of species and accessions for regeneration at four regeneration sites around Australia. A backup of accessions will be deposited into the Global Seed Vault in Svalbard, Norway in February 2018. To date 3,489 accessions have been provided to 80 researchers representing 50 institutions in 25 countries with 70% of materials supporting Australian research and development.